Soil physical quality influenced by winter plants - Goulart Machado, Rafael; Ferreira Franco, Jean; Hahn, Leandro (Scientia Agraria Paranaensis, 2021)
The biomass production by cover plants provides soil protection against erosion and weed control in the winter period, while the effect of cover crops on the parameters of physical soil quality helps in root growth and water storage. The objectives of the present study were to evaluate the influence of winter plants on the physical quality of the soil. The experiment consisted of unifactorial treatments, composed of different winter plants: vetch (Vica sativa L.), forage radish (Raphanus sativus L.), black oat (Avena strigosa Schreb.), rye (Secale cereale L.), wheat (Triticum aestivum L.) and control treatment. The experimental design was randomized blocks, with four replications per treatment. The parcels consisted of 34 lines implanted with a disc seeder and spaced 17 cm and 10 m long, comprising an area of ​57,80 m2 per parcel. Sowing densities were 40 kg ha‑1 for vetch, 20 kg ha-1 for forage radish, 60 kg ha-1 for rye, 150 kg ha-1 for wheat and 90 kg ha-1 for black oat. The control treatment consisted of the vegetation that emerged spontaneously. The parameters evaluated were plant green mass, weed occurrence, apparent density, gravimetric moisture and soil penetration resistance. With the vetch cultivation there was a reduction in the density of the soil in its surface layer, compared to the control treatment and the other cover crops. Wheat increased gravimetric soil moisture retention. Forage radish was superior to the other cover crops in terms of biomass production, totaling 59.91 t ha-1, as well as being the only cover crop that reduced soil penetration resistance, in the layer from 0 to 40 cm of ground. Vetch reduced the density of the soil in its surface layer, and also the resistance to penetration, from 21 cm of depth. Compared to the control treatment, cover crops were efficient in suppressing weed growth.